2015
DOI: 10.4081/ijfs.2015.4531
|View full text |Cite
|
Sign up to set email alerts
|

Beta emitter radionuclides (90Sr) contamination in animal feed: validation and application of a radiochemical method by ultra low level liquid scintillation counting

Abstract: 90Sr is considered as a dangerous contaminant of agri-food supply chains due to its chemical affinity with Calcium, which makes its absorption in bones easy. 90Sr accumulation in raw materials and then in final products is particularly significant in relationship to its ability to transfer into animal source products. The radionuclides transfer (137Cs and 90Sr) from environment to forages and then to products of animal origin (milk, cow and pork meats) was studied and evaluated in different studies, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Specific guidelines for validating radiochemical methods are not available. As demonstrated previously (dell'Oro et al 2014;Iammarino et al 2015), method validation can be carried out following an in-house validation model, developed according to the most representative European regulations and guidelines related to chemical methods (European Commission 2002;Thompson et al 2002;European Commission 2017;Iammarino 2019). This approach was integrated, where necessary, with specific ISO reference documents, to complete the validation relating to other radiochemical parameters (WHO and FAO 2011).…”
Section: Validation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific guidelines for validating radiochemical methods are not available. As demonstrated previously (dell'Oro et al 2014;Iammarino et al 2015), method validation can be carried out following an in-house validation model, developed according to the most representative European regulations and guidelines related to chemical methods (European Commission 2002;Thompson et al 2002;European Commission 2017;Iammarino 2019). This approach was integrated, where necessary, with specific ISO reference documents, to complete the validation relating to other radiochemical parameters (WHO and FAO 2011).…”
Section: Validation Proceduresmentioning
confidence: 99%
“…More in depth, in order to simulate the most complex analytical conditions, a matrix characterised by both high levels of possible interfering metals and detectable amounts of Sr-90 was chosen. Since the composition and possible Sr-90 contamination is highly variable among different types of feed (Iammarino et al 2015), a "mix" of several kinds of feed was prepared. Portions (175 g each) of forage, corn, bran, and complementary feed were ashed and carefully homogenised.…”
Section: Validation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore reasonable to statistically elaborate the 90 Sr activity concentrations detected in NO-MSM samples for identifying a level (''cut-off'') that may be useful for discriminating MSM from NO-MSM samples. This elaboration was conducted by using an approach similar to that reported in recently published studies (Iammarino et al 2014(Iammarino et al , 2017. A possible maximum level to suggest for this purpose was elaborated as follows: the mean value related to this group of samples (0.024 Bq kg -1 ) was added to 3r (r = 0.028 Bq kg -1 ), obtaining an activity concentration equal to 0.108 Bq kg -1 .…”
Section: Determination Of 90 Sr Activity Concentrationmentioning
confidence: 99%
“…This is due to high chemical affinity of 90 Sr with calcium. Taking into account that 90 Sr contamination of animal feeds may result significant, this accumulation may be verified representing a food safety/animal wellness concern (Iammarino et al 2015). Iammarino et al (2018) reported 90 Sr mean activity concentration of 1.4 Bq kg -1 in chicken bones.…”
Section: Introductionmentioning
confidence: 99%